FAST DISSOLVING SUBLINGUAL PATCH OF PHENOBARBITAL SODIUM: FORMULATION AND IN VITRO EVALUATION - THAYYILAKANDY, SUJAID; P. S., GAYATHRI; K. K., ARJUN; KRISHNAKUMAR, GAYATHRI; NAIR, SREEJA C. (International Journal of Applied Pharmaceutics, 2020)
Objective: To formulate and characterize. Phenobarbital sodium loaded sublingual patch using biodegradable, mucoadhesive, fast-dissolving natural polymer pullulan for immediate management of epileptic seizures. Methods: Phenobarbital sodium loaded sublingual patches were prepared by the solvent casting method and were subjected to various physicochemical evaluation parameters to find the optimized sublingual patch. The in vitro drug release study and kinetic model of the optimized formulation was also carried out. The stability study of the optimized Phenobarbital sodium loaded sublingual patch was also done. Results: From in vitro drug release study, it was found that Phenobarbital sodium loaded sublingual patch (S4) exhibited a maximum drug release of 96.24±1.27% at the end of 60 min compared to other formulations indicating a faster drug release from the formulation with release kinetics as Higuchi diffusion model. In fact, a notable release data was obtained between 0.5 to 8 min by all formulations, specifically S4 formulation (20.84±1.97% and 77.22±2.41% drug release at the end of 0.5 min and 8 min respectively) showed a better percentage release profile in comparison with other formulations. Such a trend is vital to deliver the drug at a faster rate to promote immediate effect for managing the fatal and complicated seizure. Considering the physicochemical property and in vitro drug release data, S4 formulation was regarded as an optimized one. The stability study also confirmed that S4 formulation is stable at refrigeration conditions. Conclusion: The formulated Phenobarbital sodium loaded sublingual patch is an effective drug delivery carrier which enables faster drug release to manage epileptic seizure.